Corporate governance mechanisms and earnings management in Malaysian government linked companies. The impact of GLCs transformation policy - Mohamad, Muslim Har Sani; Abdul Rashid, Hafiz Majdi; Ali Mohammed Shawtari, Fekri (2010)
As the major shareholder, Malaysian Government in 2004 has embarked on the Government linked Companies (GLCs) transformation policy program that mainly emphasizes on enhancing the corporate governance mechanisms of the State owned Enterprises (SOEs) in order to enhance effectiveness of the board. The paper aims to examine the impact of corporate governance mechanisms as embedded in the transformation program on the practice of earnings management. In particular, the study uses data for two periods of time (pre and post transformation), and examine whether the period of post transformation policy has experienced any improvement of board monitoring role in curbing earnings management activities. The main findings show that there is an increase of earnings management activities in post transformation period. Further, the findings revealed that all corporate governance mechanisms have little impact to curb earnings management activities except for board meetings and leadership structure in the post transformation period.The board meetings and separate role of two top positions in the companies were shown to have negative impact on earnings management post transformation policy and that relationship do not hold for the period pre transformation policy. Although the study has shown positive preliminary impact of tightening corporate governance in GLCs, scope to expand the research was also discussed.